William and Mabel Meed on an outing with a dogsled on frozen Lake Laberge, Yukon Territory, April 29, 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.255 [Meed journal: "My wife and I "sleighing on the lake" Lower LeBarge, April 29, 1902."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number